Artists and amateurs : etching in 18th-century France - Stein, Perrin; Guichard, Charlotte; Hoisington, Rena M.; Rudy, Elizabeth M.; Metropolitan Museum of Art (New York, N.Y.) (New York : The Metropolitan Museum of Art, 2013)
"Throughout the eighteenth century, a large number of artists-painters, sculptors, draftsmen, and amateurs-experimented with etching, a highly accessible printmaking technique akin to drawing. Some, like Antoine Watteau and Fran{cedil}cois Boucher, encountered the process within the thriving commerce of the Paris print market. Others, like Jean-Honoré Fragonard and Hubert Robert, experimented with the technique during their student years in Rome. Over the course of the century, the free and improvisational aesthetic of the etching process increasingly was embraced, and French artists looked to seventeenth-century masters, such as Rembrandt in the north, and Salvator Rosa and Giovanni Benedetto Castiglione to the south, for inspiration. The expressive potential of the technique was also explored in a more experimental manner by artists like Gabriel de Saint-Aubin and Louis Jean Desprez, who harnessed the inky tonalities of the medium to their personal and idiosyncratic vision."--The Metropolitan Museum of Art website.
Introduction / Perrin Stein -- Learning to Etch / Rena M Hoisington -- On the Market: Selling Etchings in Eighteenth-Century France / Elizabeth M Rudy -- Etching as a Vehicle for Innovation: Four Exceptional Peintres-Graveurs / Rena M Hoisington -- Diplomacy, Patronage, and Pedagogy: Etching in the Eternal City / Perrin Stein -- Amateurs and the Culture of Etching / Charlotte Guichard -- Echoes of Rembrandt and Castiglione: Etching as Appropriation / Perrin Stein -- Works in the Exhibition.
Catalog of an exhibition held at the Metropolitan Museum of Art, New York, October 1, 2013-January 5, 2014.
Includes bibliographical references (pages 222-223) and index.
Keywords: Etching, French -- 18th century -- Exhibitions; Etching -- Technique -- Exhibitions; Art, Amateur -- France -- 18th century -- Exhibitions